Penerapan Prototipe Smart Home Sederhana untuk Manajemen Energi di SMK Teknik Elektronika - Ubaidah; Despa, Dikpride; Septiana, Trisya (Nemui Nyimah, 2025)
This community service program aims to introduce the concept of smart homes and energy management through training on simple automation systems based on the Internet of Things (IoT). The target participants were students from the Electronics Engineering program at a vocational school in Bandar Lampung. Participants were trained to design and program lamp and fan control systems using an ESP32 microcontroller integrated with the Blynk application as a remote-control interface. The activity employed a learning by doing approach through socialization, workshops, and hands-on project sessions. The results indicated an improvement in students’ knowledge and skills in understanding IoT principles, automation systems, and their application for efficient electrical energy use. The developed smart home prototype successfully controlled electrical devices wirelessly via smartphones, serving as an effective and inspiring practical learning medium for fostering digital technology innovation in vocational education settings.